2018
DOI: 10.2344/anpr-65-02-03
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding Midazolam to Propofol Intravenous Sedation to Suppress Gag Reflex During Dental Treatment

Abstract: We retrospectively investigated the efficacy and safety of propofol administration alone and in combination with midazolam for gag reflex suppression during dental treatment under intravenous sedation. We included 56 patients with an overactive gag reflex who were to undergo dental treatment under intravenous sedation. They were divided into propofol (P group, n = 22) and midazolam with propofol (MP group, n = 34) groups. The P group received propofol alone, while the MP group received midazolam (0.04 mg/kg) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…It should be noted that men, patients who underwent multiple dental procedures, and patients who received multiple sedation drugs were more likely to have side effects. Although previous studies have indicated that unfavorable side effects are small, [ 11 14 ] the absolute percent of side effects by sedation type was first reported in this study based on our large clinical surveillance.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…It should be noted that men, patients who underwent multiple dental procedures, and patients who received multiple sedation drugs were more likely to have side effects. Although previous studies have indicated that unfavorable side effects are small, [ 11 14 ] the absolute percent of side effects by sedation type was first reported in this study based on our large clinical surveillance.…”
Section: Discussionmentioning
confidence: 67%
“…A previous study also demonstrated that the use of intravenous conscious sedation with propofol only versus midazolam with propofol did not differ with regard to treatment time in general dental patients. [14] This study has some limitations. First, the procedures were not designed according to the objective of the study because this was a retrospective study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In recent years, propofol has been used as an alternative way of reducing postoperative nausea and vomiting due to its antiemetic and anticonvulsant therapeutic properties [11] [12]. Due to its quick plasma clearance, it acts quickly but only lasts a short time [13] [14]. Rosillo-Menesesa et al demonstrated that propofol primarily acts on GABA receptors by increasing chloride ion conduction.…”
Section: Antiemetic Effect Of Propofolmentioning
confidence: 99%
“…Intravenous sedation has been widely used in dental procedures to minimize these unpleasant conditions (5,6). Advantages of this sedation method may include reduced patient anxiety (7-9), reduced post-operative pain (10), increased patient and surgeon satisfaction (11) and suppressed gag reflex (12). Propofol is the most commonly used intravenous anesthetic.…”
Section: Introductionmentioning
confidence: 99%